2019
DOI: 10.1136/injuryprev-2019-043307
|View full text |Cite
|
Sign up to set email alerts
|

Drowning mortality in children aged 0–14 years in Victoria, Australia: detailed epidemiological study 2001–2016

Abstract: BackgroundMajor reductions in child drowning mortality rates have been observed historically in Victoria, Australia, for the period 1863–2000. Despite this trend, drowning remains the leading cause of unintentional child death in Victoria. This study investigates the residual fatal drowning problem in the Victorian child population (0–14 years) for the period 2001–2016.AimsDescribe the epidemiology of child drowning deaths in the Victorian population in 2001–2016; investigate risk factors and direct antecedent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 24 publications
6
23
0
Order By: Relevance
“…In the retrospective analysis, we were only able to collect limited sociodemographic data (gender and age). These are congruent with the literature [ 1 , 35 , 36 ]. We emphasize the importance to include such sociodemographic data in further investigations as they could be important factors to improve specific prevention measures.…”
Section: Discussionsupporting
confidence: 93%
“…In the retrospective analysis, we were only able to collect limited sociodemographic data (gender and age). These are congruent with the literature [ 1 , 35 , 36 ]. We emphasize the importance to include such sociodemographic data in further investigations as they could be important factors to improve specific prevention measures.…”
Section: Discussionsupporting
confidence: 93%
“…A study in Australia showed that inadequate care and lapses in supervision, such as indoor housework, outdoor housework, and talking/socializing, were major contributors to child drowning [20]. We also found that caregivers were occupied with housework, phone calls or socializing at the time of the drowning.…”
Section: Discussionmentioning
confidence: 63%
“…There were 19 studies which reported factors. 12,20,22,23,[25][26][27][28][29][32][33][34][35]38,39,41,42,44,46 With respect to age, children were identified as being significantly more likely to drown in rural areas of Victoria, in particular 10-to 14-year-olds, 33 while children around the age of two were deemed at risk of drowning in rural water hazards in Queensland, often due to wandering. 34 Children under five were also identified at significantly increased risk of drowning in portable pools if they resided in very remote areas.…”
Section: Common Factorsmentioning
confidence: 99%
“…Factors linked to drowning risk in rural areas included rivers, 22 alcohol 46 and children's unsupervised access to water. 31,33 There was no indication in the literature that urban-based solutions worked or did not work in rural locations.…”
Section: Very Remotementioning
confidence: 99%